The TAM-TB Assay—A Promising TB Immune-Diagnostic Test With a Potential for Treatment Monitoring - Ahmed, Mohamed I. M.; Ziegler, Christian; Held, Kathrin; Dubinski, Ilja; Ley-Zaporozhan, Julia; Geldmacher, Christof; von Both, Ulrich (Frontiers in Pediatrics, 2019)
Tuberculosis (TB) epidemiology is changing in Western and Central Europe due to the rise in immigration and refugees fleeing high-TB-burden areas of war and devastation. The change in local demography and the lack of sensitive and specific TB diagnostic and monitoring tools, especially for cases of childhood TB, leads to either missed cases or over-treatment of this group. Here we present a promising new diagnostic approach, the T cell activation marker (TAM)-TB assay, and its performance in a case of extra-pulmonary TB occurring in a 16 year old refugee from Afghanistan. This assay is based on the characterization of 3 activation markers (CD38, HLA-DR and Ki67) and one maturation marker (CD27) on M. tuberculosis-specific CD4 T cells. It was performed at time-points T0 (10 days), T1 (1 month), T2 (6 months) and T3 (12 months) post-treatment initiation. All markers were able to detect active tuberculosis (aTB) within this patient at T0 and reverted to a healthy/LTBI phenotype at the end of treatment. Tantalizingly, there was a clear trend towards the healthy/LTBI phenotype for the markers at T1 and T2, indicating a potential role in monitoring anti-TB treatment in the future. This assay may therefore contribute to improved TB diagnostic algorithms and TB treatment monitoring, potentially allowing for individualisation of TB treatment duration in the future.